2018
DOI: 10.12944/cwe.13.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Hazards and Musculoskeletal Disorders Among Workers of Health Care Facilities

Abstract: The present study is conducted to determine occupational health and safety hazards with special focus on ergonomic hazards among healthcare facility (HCF) workers. A structured questionnaire survey was conducted among 200 workers in five HCFs of Lahore, Pakistan. Among the reported ergonomic hazards, muscle aches/ sprains (76.5%), elbow/ wrist/ neck pain (56.0%), body posture issues (56.0%), excessive stretching of muscles (67.5%) and bending/ twisting at work (55.5%) were commonly encountered. Biological haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Working in FMC Yenagoa was a predisposing factor of exposure to physical hazards with 2 times a higher rate than owerri. Physical hazards included slips, trips/falls, high noise levels, radiation and excessive heat, a study revealed exposure of HCWs to slips /trips/falls with a frequency of 65.0%, high noise levels 64.0%, exposure to radiation 51.5% (Hamid, et al 2018) which is quite consistent with this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Working in FMC Yenagoa was a predisposing factor of exposure to physical hazards with 2 times a higher rate than owerri. Physical hazards included slips, trips/falls, high noise levels, radiation and excessive heat, a study revealed exposure of HCWs to slips /trips/falls with a frequency of 65.0%, high noise levels 64.0%, exposure to radiation 51.5% (Hamid, et al 2018) which is quite consistent with this study.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of an infection control team is also a control, 73% of HCWs in FMC Owerri indicated that an infection control team existed in the facility while just 56% in FMC Yenagoa, the efficiency of these teams are questionable as the results do not show much impact, they may just be functional during outbreaks but also laid back in their actions due to lack of funding as the final decisions lie with management. [27]. In another study in India 59% reported repeated bending and twisting, 42% heavy lifting, 44% chairs with no back rests and 37% standing long hours in ergonomic hazards [28].…”
Section: Discussionmentioning
confidence: 98%
“…Working in multiple healthcare facilities, increased frequencies and duration of shifts per day, and working overtime has been reported to be significantly associated with the increased risk of developing musculoskeletal disorders among healthcare workers and increased exposure to the different healthcare-related ergonomic hazards. 6,12,15 This has been furtherly indicated in a previous comparative investigation that included nurses that were either involved in full or part-time shifts. The authors concluded that nurses that were involved in the part-time shifts significantly had less frequent workrelated fractures and injuries than those that were involved in full-time shifts.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous crosssectional investigation in Pakitan, Hamid et al estimated that the prevalence of muscle aches, neck, wrist/elbow pain, muscle stretching, twisting, and harmful postures were 76.5%, 56%, 67.5%, 55.5%, and 56%, respectively. 6 Furthermore, it has been estimated that chronic back pain, carpal tunnel syndrome, fracture-related injuries, hamstring pain, lifting heavy objects were prevalent among 46.5%, 27%, 22.5%, 26%, and 50% of the included healthcare workers, respectively. The reported prevalence rates among the different investigations in the literature regarding musculoskeletal disorders among healthcare workers across the different clinical settings were found to be remarkably variable.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Approximately 59 million healthcare workers around the globe are exposed to ergonomic hazards daily. 2,7 According to the International Ergonomics Association, ergonomics is defined as a "scientific discipline that applies theory, principles, data, and methods to optimise human well-being. It evaluates tasks, jobs, environments, and systems to make it compatible with the needs, abilities, and limitations of people".…”
mentioning
confidence: 99%